2000
DOI: 10.1002/(sici)1097-0282(20000405)53:4<308::aid-bip3>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the HIV-1 and ASV integrase active sites upon metal cofactor binding

Abstract: The HIV‐1 integrase, which is essential for viral replication, catalyzes the insertion of viral DNA into the host chromosome thereby recruiting host cell machinery into making viral proteins. It represents the third main HIV enzyme target for inhibitor design, the first two being the reverse transcriptase and the protease. We report here a fully hydrated 2 ns molecular dynamics simulation performed using parallel NWChem3.2.1 with the AMBER95 force field. The HIV‐1 integrase catalytic domain previously determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The mapping of the electrostatic potential onto (or near) the molecular surface has been widely used in biomolecular simulations since it is particularly useful in the understanding of molecular interactions. [31][32][33][34] Formally, the electrostatic potential has contributions from the n nuclei and the electrons represented by the electron density . It can be written as:…”
Section: -29mentioning
confidence: 99%
“…The mapping of the electrostatic potential onto (or near) the molecular surface has been widely used in biomolecular simulations since it is particularly useful in the understanding of molecular interactions. [31][32][33][34] Formally, the electrostatic potential has contributions from the n nuclei and the electrons represented by the electron density . It can be written as:…”
Section: -29mentioning
confidence: 99%
“…The largest (amino acids 50 -207 in ASV IN) is the central catalytic core domain (CCD or "core"). This domain contains the DD(35)E motif of acidic residues that coordinate the required divalent metal ions, Mg 2ϩ or Mn 2ϩ (3)(4)(5)(6). The isolated HIV IN core domain forms a dimer in solution (7), and the three-dimensional structure of the core from several retroviral IN proteins has been solved by x-ray crystallography of either the isolated domain or two-domain fragments that include the N-(NTD) or C-terminal (CTD) domains (8 -14).…”
mentioning
confidence: 99%
“…Structural studies of IN revealed a single binding site for Mg 2ϩ and Mn 2ϩ (20,35), while two Cd 2ϩ or Zn 2ϩ ions separated by 3.6 to 3.7 Å were observed (4,5,49). Indeed, it is believed that a second Mg 2ϩ ion is carried into the integrase active site by the substrate (31).…”
mentioning
confidence: 99%